Advances in 1, 3, 5-triazepines chemistry. Issue 43 (15th April 2016) - Elattar, Khaled M.; Mert, Başak Doğru; Abozeid, Mohamed A.; El-Mekabaty, Ahmed
Abstract : This study reported the chemistry of 1, 3, 5-triazepines. Heterocyclic 1, 3, 5-triazepines are mono and fused cycles. Abstract : This review describes a literature survey of 1, 3, 5-triazepines. The investigated heterocycles were the monocyclic and fused 1, 3, 5-triazepines. The different sections of the paper cover: theoretical methods, spectroscopy aspects, thermodynamic aspects, synthesis and reactions of the monocyclic and fused heterocycles incorporated into the 1, 3, 5-triazepine moiety. The biological evaluation of the target compounds are also described as well as their synthetic applications. The reaction mechanisms are discussed.